REVAMPING MANAGEMENT EDUCATION: THE POWER OF PROJECT-BASED LEARNING - Friscilla Wulan Tersta1; Linardo Pratama; Riri Ardianti; Firman (PT. Jurnal Center Indonesia Publisher, 2026)
Project-Based Learning (PjBL) has emerged as an innovative educational approach that bridges the gap between theoretical knowledge and practical application. This study explores the impact of PjBL on students' learning experiences, particularly in real-world engagement, collaborative teamwork, social interaction, and problem-solving skills. Findings from interviews with multiple informants highlight that PjBL provides students with new experiences beyond the traditional classroom setting, allowing them to engage directly with the school environment. Through collaborative projects, students develop interpersonal skills, enhance communication, and strengthen teamwork. Additionally, PjBL fosters adaptability and problem-solving abilities, equipping students with essential 21st-century competencies. These results align with the theoretical perspectives of Krajcik & Blumenfeld (2006) and Blumenfeld et al. (1991), which emphasize the significance of experiential learning and social interaction in deepening students’ understanding. Overall, PjBL offers a transformative learning experience by making education more meaningful, engaging, and relevant to real-world challenges